Power relationships in gender-related disclosures: exploring language in selected Fortune 500 companies’ sustainability reports - Hossain, Dewan Mahboob; Nik Ahmad, Nik Nazli; Siraj, Siti Alawiah (Inderscience Publisher, 2017)
This research investigates power relationships in the disclosure on women and gender related issues in corporate sustainability reports. For this purpose fifty two companies from the 2013 Fortune top 100 list were selected. Critical discourse analysis (CDA) was conducted on the basis of Fairclough’s (1989) framework. Fairclough suggested analysing the language from three dimensions: text, process and social. Through CDA the notions of power and hegemony were identified and explained with the help of Bourdieu’s cultural capital as suggested by Everett (2004) and Aaken et al. (2012). The research concludes that discourses on women and gender carry the traditional patriarchal notions and reflect traditional ideas about women prevailing in most of the societies. Women were presented as a distressed species and companies tried to portray themselves as the saviours of women. The findings of this research contribute to the critical accounting literature by highlighting the strategic use of language in relation to gender issues by large global corporations.